Efficient authoring of software documentation using RaPiD7 - Kylmakoski, Roope (International Conference on Software Engineering: Proceedings of the 25th International Conference on Software Engineering : Portland, Oregon; 03-10 May 2003, 2003)
This paper presents a method, developed in Nokia, for efficient document authoring in software development projects. The method is called RaPiD7 (Rapid Production of Documentation, 7 steps). The method improves traditional approach for document authoring in which work is typically started by informal initiative, and the actual writing of a document is a task performed by a single individual. Traditional document authoring usually relies on inspections to verify the quality of the documentation. RaPiD7 addresses the document authoring problem by getting people involved in the documentation work earlier as a team in order to guarantee quality, calendar time efficiency, commitment and improved communication. This paper also compares RaPiD7 with some other similar approaches and presents results from a large-scale experiment with RaPiD7.